Pengaruh Positif Perceived Service Quality, Perceived Price Fairness Terhadap Consumer Loyalty Di Mediasi Oleh Consumer Satisfaction Pada Customer Restaurant Fast Food (Universitas Gresik, 2023)
This study aims to determine the effect of perceived service quality, perceived price fairness on customer loyalty mediated by customer satisfaction at fast food restaurant customers in South Jakarta. In collecting data, this study used a sample of restaurant customers in South Jakarta. The sample used was 122 respondents. The data analysis technique uses Structural Equation Modeling (SEM) with the help of the AMOS computer program. The results of this study indicate that perceived service quality, perceived price fairness on brand loyalty has a positive effect mediated by customer satisfaction at fast food restaurant customers in South Jakarta, which means that in this study perceived service quality, perceived price fairness on brand loyalty as a mediating effect on customer satisfaction